A practical approach for the porting of the Ravenscar profile from ADA to C: method, rules adaptation and supporting tools. (10th April 2023) - Rinaldi, Claudia; Romano, Fabio; Serri, Paolo; Tiberi, Luca
While conceiving with hard real time systems, determinism is the main requirement that must be satisfied in order to properly predict their behaviour as required by their definition. For achieving this purpose an available solution is restricting Ada language tasking features to the Ada Ravenscar profile subset. This paper presents a solution to apply the Ravenscar profile concepts in systems where the tasking management is based on RTEMS real-time operating system, and C and Ada languages are used together. Moreover, a SW tool to automatically check the compliance with Ravenscar is proposed and the outcomes of some experimental activities proving the effectiveness of the SW tool are discussed.